2020
DOI: 10.1038/s41467-020-19671-3
|View full text |Cite
|
Sign up to set email alerts
|

Dominant subtype switch in avian influenza viruses during 2016–2019 in China

Abstract: We have surveyed avian influenza virus (AIV) genomes from live poultry markets within China since 2014. Here we present a total of 16,091 samples that were collected from May 2016 to February 2019 in 23 provinces and municipalities in China. We identify 2048 AIV-positive samples and perform next generation sequencing. AIV-positive rates (12.73%) from samples had decreased substantially since 2016, compared to that during 2014–2016 (26.90%). Additionally, H9N2 has replaced H5N6 and H7N9 as the dominant AIV subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 67 publications
(89 reference statements)
4
115
0
Order By: Relevance
“…These observations indicate a potential mammalian adaptation of H5N6 AIV. Fortunately, our results showed that DG/19 possessed 226Q and 228G (H3 numbering) in the HA, which suggested a typical avian receptor preference and were consistent with previous studies [ 16 ]. However, DG/19 has 222Q and 227R in the HA, which has been shown to facilitate virus binding to fucosylated sialosides [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These observations indicate a potential mammalian adaptation of H5N6 AIV. Fortunately, our results showed that DG/19 possessed 226Q and 228G (H3 numbering) in the HA, which suggested a typical avian receptor preference and were consistent with previous studies [ 16 ]. However, DG/19 has 222Q and 227R in the HA, which has been shown to facilitate virus binding to fucosylated sialosides [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…A further comparison with the reference sequence of the sub-clades of 2.3.4.4 suggested DG/19 belongs to the 2.3.4.4 h subclade. The internal genes of DG/19 had high identity with strains isolated from ducks in 2017–2018 in Hunan by a recent study [ 16 ]. The HA gene has the highest nucleic acid homology with A/duck/Hunan/1.12_YYGK 72H3-OC/2018(H5N6) (98.35%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations